2017
DOI: 10.1097/eja.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography and passive leg raising in the postoperative period

Abstract: This is the first study showing that measurement of CO after PLR can predict volume response in spontaneously breathing postoperative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…In recent years, bedside ultrasonography has been considered as a noninvasive, real-time, convenient, low-cost, and repeatable tool for monitoring hemodynamics [10,11,[19][20][21]. Previous studies have con rmed that echocardiography was highly correlated with PICCO in CO and SV, and PLR combined with non-invasive ultrasound has signi cant advantages in evaluating FR, which can be determined by monitoring SV and aortic blood ow [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, bedside ultrasonography has been considered as a noninvasive, real-time, convenient, low-cost, and repeatable tool for monitoring hemodynamics [10,11,[19][20][21]. Previous studies have con rmed that echocardiography was highly correlated with PICCO in CO and SV, and PLR combined with non-invasive ultrasound has signi cant advantages in evaluating FR, which can be determined by monitoring SV and aortic blood ow [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Passive leg raising (PLR) is a simple repeatable self-replenishing uid method done to shift venous blood from the lower limbs toward the intrathoracic compartment [8,9]. Transthoracic Doppler echocardiography (TTE ) is a non-invasive method that allows for real-time monitoring of the descending aortic blood ow, and the estimation of SV [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, bedside ultrasonography has been considered as a noninvasive, real-time, convenient, low-cost, and repeatable means of hemodynamic monitoring [10,11,[19][20][21]. Previous studies have confirmed that echocardiography was highly correlated with PICCO in CO and SV, and PLR combined with non-invasive ultrasound has significant advantages in evaluating FR, which can be determined by monitoring SV and aortic blood flow [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Passive leg raising (PLR) is a repeatable self-replenishing fluid method by shifting venous blood from the lower limbs toward the intrathoracic compartment [8,9].Transthoracic Doppler echocardiography ( TTE ) is a non-invasive method that allows for real-time monitoring of the descending aortic blood flow, and the estimation of SV [10,11]. Therefore, using the bedside ultrasound to measure the variation of SV induced by PLR may be used to evaluate FR in these children patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic echocardiographic parameters, especially CO variation due to volume infusion or volume shift after PLR, are excellent predictors of volume responsiveness. 14,1619 CO is the amount of blood pumped by the heart per minute and is dependent on the heart rate, myocardial contractility, preload, and afterload. In healthy individuals, the right and left ventricles pump the same volume of blood, therefore, measurements of left and right ventricular CO are equal.…”
Section: Discussionmentioning
confidence: 99%